Enhancing Islamic Name Selection: A Decision Support System Utilizing Analytical Hierarchy Process Methodology - Taufik Ashraf Zaid (Journal Basic Science and Technology, 2024)
This research presents the development of a Decision Support System (DSS) tailored for the selection of Islamic names using the Analytical Hierarchy Process (AHP) methodology. Naming holds profound cultural and religious significance in Islamic tradition, reflecting values, beliefs, and aspirations. The DSS integrates data analytics, mathematical modeling, and cultural sensitivity to provide a systematic approach to name selection, encompassing criteria such as religious significance, linguistic aesthetics, and cultural relevance. Through a thorough review of existing literature, the research identifies gaps in knowledge and explores the intersection of technology and tradition in name selection. The methodology encompasses problem formulation, criteria identification, alternatives generation, hierarchical structure design, pairwise comparisons, AHP model development, system development, testing and evaluation, validation and verification, and documentation and reporting. A numerical example illustrates the application of the DSS, demonstrating its effectiveness in prioritizing Islamic names based on predefined criteria. The findings highlight the importance of considering multiple dimensions in name selection and the potential of the DSS to empower Muslim individuals and families in making informed and culturally sensitive choices. The research contributes to advancing knowledge and understanding in this domain, offering insights into the complexities and nuances of name selection in Islamic culture.